Sistem Presensi Karyawan Dengan Teknologi GPS Berbasis Web (Studi Kasus PT. Mersifarma) - Rizaldi, Fazrin Muhammad; Hermanto, H; Fergina, Anggun (STIKOM Tunas Bangsa Pematangsiantar, 2023)
Discipline is one of the sources of employee performance appraisal of an organization or agency. Discipline is divided into 2 (two), namely discipline on time and discipline on behavior or actions in carrying out work which has an impact on job satisfaction, safety, productivity, and organizational stability. Attendance is a model for recording the hours of arrival and departure of a person. Attendance is generally used in a formal environment such as school or work. The purpose of using attendance is to monitor attendance data as well as a means to measure a person's level of discipline. This is of course quite important, especially in the work environment, because if a company has disciplined employees, the productivity level of the company will be even greater. There are various methods of doing attendance, ranging from recording data manually, through a finger print machine, or through the system. In general, an agency in the world of work prefers to use a finger print machine in doing attendance. This is based on the cheapness of the technology if implemented in the world of work. PT. MERSIFARMA initially used a finger print machine to perform attendance. However, the presence of the Corona virus (Covid-19) in 2020 certainly has an impact on the attendance system that uses finger print media. This is because the virus can be transmitted through fingerprints. On the basis of this problem, the researchers tried to develop a web-based attendance system application and raised it as a research. This application is expected to be able to minimize the risk of contracting the virus in the office environment. In addition to this, this system is also expected to be able to assist HRD in processing attendance data easily and in real time.